Holistic Switchers: The Spiritual and Value Commitments of a Group of Older Women Church Leavers - Eccles, Janet (Journal for the Study of Spirituality, 2011)
This article considers a group of older women who have disaffiliated from the Christian church at some time in their past and who have turned to holistic spiritual practices. I characterize these women as ‘Seekers’ in that they combine their practice with freely chosen elements of Christian beliefs, texts and rituals, albeit much readapted and reinterpreted. A further dimension, however, is shown in their practice of the ethic of care. This value commitment, to friends and family, and those in need, continues as very much part of their present identity despite the changes in their religious and spiritual commitments.